Permasalahan Sekolah Modern dan Tantangan yang Dihadapinya - Dhani, Alya Rahma; Lestari, Indah Bunga; Vidia, Vivi Egi; Ananda, Dian Ovi (Lembaga Yasin AlSys, 2023)
This article discusses the challenges faced by modern schools in providing quality education and the challenges they must overcome to address these issues. Common problems in modern schools include overloaded curriculum, technological dominance, excessive workload, and limited facilities and infrastructure. One major issue is an overloaded curriculum, where students face pressure to absorb a vast amount of information within limited timeframes, leaving little room for the development of their interests and talents. Technological dominance also has a significant impact, as excessive reliance on technology can reduce social interaction and hinder students' critical thinking abilities. Excessive workload is another commonly faced problem for students in modern schools, resulting in stress and an imbalance between academic activities and personal life. Additionally, limitations in facilities and infrastructure, such as inadequate facilities and insufficient infrastructure, can restrict students' learning experiences. The challenges faced by modern schools include the development of relevant and flexible curricula, as well as the wise integration of technology to optimize learning. Managing a balanced workload for students and improving school facilities and infrastructure are also challenges that need to be addressed. In addressing these challenges, collaboration among schools, teachers, parents, and relevant stakeholders is key. Continuous teacher training, the implementation of innovative teaching models, and adequate funding are necessary to achieve sustainable improvements in education. Through a deep understanding of the problems faced by modern schools and the challenges they encounter, it is hoped that this article will provide valuable insights for stakeholders in addressing educational issues and promoting better progress for students and society as a whole.